2020
DOI: 10.20944/preprints202012.0800.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Barriers to Enablers: The Role of Organizational Learning in Transitioning SMEs into the Circular Economy

Abstract: To contribute to small and medium enterprises (SMEs) sustainable transition into the circular economy, the study proposes the activation of organizational learning (OL) processes – denoted here as multi-level knowledge creation, transfer, and retention processes – as a key phase in introducing circular business models (CBMs) at SME and supply chain (SC) level. The research employs a mixed-method approach, using the focus group methodology to identify contextual elements impacting on CBM-rel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
(181 reference statements)
0
4
0
Order By: Relevance
“…According to Vihma and Moora (2020), to perform successfully circular design capacity and capability, critical dimensions for Romanian SMEs are relevant strategy and planning, network integration, learning process, and owners and managers' leadership. Regarding CBM‐related organisational learning, Scipioni et al (2021) identified the elements of the contextual factor that influence this process and evaluated the most frequent processes in Italian SMEs in the construction sector. Contextual factors, specifically cultural, regulatory, structural, and process factors, can be considered both drivers and barriers and are presented in three dimensions—external environment, supply chain, and SME.…”
Section: Resultsmentioning
confidence: 99%
“…According to Vihma and Moora (2020), to perform successfully circular design capacity and capability, critical dimensions for Romanian SMEs are relevant strategy and planning, network integration, learning process, and owners and managers' leadership. Regarding CBM‐related organisational learning, Scipioni et al (2021) identified the elements of the contextual factor that influence this process and evaluated the most frequent processes in Italian SMEs in the construction sector. Contextual factors, specifically cultural, regulatory, structural, and process factors, can be considered both drivers and barriers and are presented in three dimensions—external environment, supply chain, and SME.…”
Section: Resultsmentioning
confidence: 99%
“…The current study can be seen as a continuation of the literature on the construction of theoretical frameworks based on a mix of well-known RBV theory (Arulrajah & Opatha, 2016) and OL theory (Scipioni, Russ, & Niccolini, 2021). Despite the fact that both theories have been thoroughly explored, the authors hope to contribute to the field by linking the structures from both theories in this work.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The current study can be considered as a continuation of previous research on the development of theoretical frameworks based on a combination of the well-known resource-based perspective theory (Arulrajah, Opatha & Nawaratne, 2015) and organizational learning theory (Scipioni, Russ & Niccolini, 2021). This can also be seen as a response to the request for a more empirical study on SMEs' long-term success that takes into account the circumstances of developing countries.…”
Section: Theoretical Implicationmentioning
confidence: 99%